The Application of the SMART Method as a Decision Support System in Determining Majors at Budi Mulia Private High School Tumbajae - Kadin Darlianto Tinambunan; Jonson Manurung (Putaka Timur Publisher, 2021)
Budi Mulia Tumbajae Private High School is one of the Catholic schools located in Tumbajae Village, Manduamas District, Central Tapanuli Regency. Which is managed by the Congregation of Brothers Budi Mulia Lourdes which has been Accredited B until now. One activity that is very important and must be carried out by high school students in the selection of majors. The selection of majors is one of the placement or distribution processes in the selection of teaching programs for students at the high school level, as happened at Budi Mulia Tumbajae High School. Students are confused in choosing what major they will choose according to the talents and abilities they have, most of the determination of the major is determined based on 3 factors. Namely: First, based on recommendations from parents. Second, The selection of majors is based on the follow-up of friends and based on the trend of majors at that time. The third is the interests and talents of the students themselves. Determinants of majors based on these three factors will certainly make regrets for students whose majors do not match their expectations of those majors, (Dani, Tingastuti, & Bayu, 2019). In choosing this major, students are allowed to choose what major they will choose, for example, whether to choose a science or social studies major. The selection of this major is intended so that students can complete school according to their interests and abilities before continuing to a higher level, namely college. To overcome the confusion of the choice of majors.